2010
DOI: 10.1177/0748233710369124
|View full text |Cite
|
Sign up to set email alerts
|

Di-butyl phthalate—induced hypomethylation of the c-myc gene in rat liver

Abstract: Peroxisome proliferators (PPs)-induced DNA hypomethylation has been proposed as a mechanism of their toxicity, including carcinogenic action. The effect of di-butyl phthalate (DBP), a known peroxisome proliferators, on the methylation level of the c-myc promoter region in rat liver was studied. Changes in the methylation status of the c-myc gene were correlated with changes in DNA synthesis, DNA methyltransferase (DNMTs) activity and liver weight. Male Wistar rats received DBP in one, three or fourteen daily o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…Similarly, rats exposed to DBP showed an increase in MYC expression level in the liver, and increased MYC expression was associated with DNA repair and synthesis [37]. The molecular mechanism by which MYC interacts with its partner, Max, acting as a transcription activator is well understood [38], while their transcription repression by MYC is not yet fully resolved.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, rats exposed to DBP showed an increase in MYC expression level in the liver, and increased MYC expression was associated with DNA repair and synthesis [37]. The molecular mechanism by which MYC interacts with its partner, Max, acting as a transcription activator is well understood [38], while their transcription repression by MYC is not yet fully resolved.…”
Section: Discussionmentioning
confidence: 97%
“…Human epidemiological studies correlated higher urinary levels of phthalate metabolites with altered imprinted gene and LINE-1 methylation in placental tissue [75,76]. Rodent studies have reported altered global and locus-specific DNA methylation following di(2-ethylhexyl)phthalate (DEHP) exposure [77,78]. Additionally, DNMT and methyl-CpG binding proteins were affected in various tissue types upon DEHP exposure in rodents [73,79].…”
Section: Bpa Phthalates and Parabens: Modes And Mechanisms Of Acmentioning
confidence: 99%
“…Although animal studies have demonstrated consistent effects of phthalates on both global and site-specific methylation (Kang and Lee, 2005; Kostka et al, 2010; Martinez-Arguelles and Papadopoulos, 2015; Pogribny et al, 2008; Wu et al, 2010), data in human populations are more limited. Prenatal urinary phthalate metabolite concentrations have been associated with methylation of imprinted genes H19 and IGF2 (LaRocca et al, 2014) and LINE-1 repetitive elements (Zhao et al, 2015) in placental tissue.…”
Section: Introductionmentioning
confidence: 99%